Alternative therapy in pregnant women with a diagnosis of luteal insufficiency. - Loayza, Nilo (2015)
Luteal insufficiency is a known cause of infertility (early abortions). The aim of this work is to offer a therapeutic alternative to carrying pregnant patients luteal insufficiency. The ideal treatment should be based on chemically pure progesterone, which we lack in our midst. Progestogens, which constitute the alternative therapy, are currently known to have efectos luteolíticos. The corpus luteum function in human can be defined in terms of quantity and duration of steroidogenic synthesis of progesterone and estrogen. These two hormones reflect the activity of different cell types at the level of the corpus luteum was observed and they can vary independently during the luteal phase.